Comparativo de fungicidas para control químico de Stemphyllium Solani en el cultivo de Tomate en el fundo Aucaloma en Lamas – San Martín - Villanueva Castillo, Elton John (2013)
The present thesis entitled "Comparison of fungicides for chemical control of Stemphyllium solani in tomato cultivation in Fundo Aucaloma Lamas-San Martin" and was aimed to evaluate and compare the effectiveness and efficiency of the fungicides in tomato crop using the variety Rio Grande. The present research work was carried out from August to December 2009, and was used Completely Randomized Block Design with 6 treatments and 3 blocks. The results obtained indicate that all strategies studied have had 100% incidence of leaf blight disease caused by Stemphylluim solani after 50 days of transplantation. Strategies 1, 2, and 3, were less severe (37,333, 39,412, 39,787 AFA), at 70 days after transplanting healthy leaf area showing greater efficiency and better control of leaf blight disease or gray stain Tomato leaf caused by the fungus Stemphyllium solani. Strategies that showed higher number of fruits were, 1 (25,467), 2 (24,800), 3 (24,667) and 4 (24,533), respectively. Strategies 1, 2, 3, achieved greater weight and the highest yield per plant were the strategies 2 with (2,147 kg), 3 (2,133 kg), and 1 (2,060 kg).